Venecuēlas ārpolitika Ugo Čavesa laikā - Žurovskis, Renārs (Latvijas Universitāte, 2014)
Maģistra darbā „Venecuēlas ārpolitika Ugo Čavesa laikā” tiek pētītas prezidenta Ugo Čavesa populisma iezīmes Venecuēlas valsts ārpolitikas veidošanā, analizējot Ugo Čavesa runas un izteikumus. Darbā tiek apskatītas populisma teorijas, pazīmes un raksturotas populisma kopīgās un atšķirīgās īpašības. Maģistra darba mērķis ir – aplūkot Venecuēlas prezidenta Ugo Čavesa kā Latīņamerikas populisma pārstāvja ideoloģiskos uzskatus un to praktisko pielietojumu izpētot, vai populistiskā ideoloģija tika izmantota arī Venecuēlas ārpolitikā. Darba izvirzītā hipotēze ir: Prezidenta Ugo Čavesa ārpolitikā ir novērojamas populisma pazīmes, kura darba gaitā tiek pierādīta. Darbā tiek izmantota Kasa Mudes populisma definīcija un teorētiskās atziņas par populismu dažādos reģionos. Tekstu analīzei tika izmantota konstruktīvistu teorija starptautisko attiecību pētniecībā un Kirka Havkinsa veiktā Ugo Čavesa runu analīze. Balstoties uz darba teorētisko daļu, empīriskajā daļā tika pierādīts un secināts, ka Ugo Čavesa ārpolitika tiek veidota ar populisma pazīmēm.

The Master’s thesis ”Venezuela`s foreign policy during Hugo Chavez`s presidency” studies populism tendencies of the president Hugo Chavez in foreign policy making of Venezuela, analyzing speeches and statements of Hugo Chavez. Populism theories, signs are discussed, as well as common and differing populism traits are characterized. The aim of the Master’s thesis is to consider the ideological views of the president of Venezuela Hugo Chavez as a representative of the Latin American populism and their practical application, finding whether populist ideology had been used also in the foreign policy of Venezuela. Hypothesis: Populism features are observed in the foreign policy of the president Hugo Chavez; the hypothesis is proved. The populism definition and theoretical statements of Cas Mudde about populism in different regions are used in the thesis. For text analysis the constructivist theory in international relations research and analysis of Hugo Chavez speeches made by Kirk Hawkins were used. Based on the theoretical part of the thesis, it was proved and concluded in the empirical part of the thesis that the foreign policy of Hugo Chavez is being made with indications to populism signs. Hypothesis: Populism features are observed in the foreign policy of the president Hugo Chavez; the hypothesis is proved. The populism definition and theoretical statements of Cas Mudde about populism in different regions are used in the thesis. For text analysis the constructivist theory in international relations research and analysis of Hugo Chavez speeches made by Kirk Hawkins were used. Based on the theoretical part of the thesis, it was proved and concluded in the empirical part of the thesis that the foreign policy of Hugo Chavez is being made with indications to populism signs.
Venezuela`s foreign policy during Hugo Chavez`s pre
Keywords: Politikas zinātne (politoloģija)